Investigation of optoelectronic characteristics of indium composition in InGaN-based light-emitting diodes. (28th January 2019) - Usman, Muhammad; Mushtaq, Urooj; Zheng, Dong-Guang; Han, Dong-Pyo; Muhammad, Nazeer
Abstract: We report a detailed numerical analysis of the optoelectronic characteristics of the indium composition on the device performance. The analysis includes discussion of the band-bending, built-in field, carrier confinement and emission spectra. The quantum well tilts strongly with increasing composition of indium. In addition, as the indium concentration increases in the active region, the spontaneous emission decreases and its full width at half maximum increases gradually.